Effects of self-controlled knowledge of performance on motor learning and self-efficacy: A kinematic study - Makki Rezvaneh; Abdoshahi Maryam; Ghorbani Saeed (Biomedical Human Kinetics, 2021)
Study aim: To evaluate the effects of providing the learners with self-controlled knowledge of performance (KP) on motor learning and self-efficacy (SE) in a dart-throwing motor task.